A Sodium–Antimony–Telluride Intermetallic Allows Sodium‐Metal Cycling at 100% Depth of Discharge and as an Anode‐Free Metal Battery (Adv. Mater. 1/2022). Issue 1 (7th January 2022) - Wang, Yixian; Dong, Hui; Katyal, Naman; Hao, Hongchang; Liu, Pengcheng; Celio, Hugo; Henkelman, Graeme; Watt, John; Mitlin, David
Abstract : Anode‐Free Batteries In article number 2106005, Hui Dong, David Mitlin, and co‐workers report an intermetallic for anode‐free batteries. The winter scene shows a birthday cake with lit candles that are melting: the cake represents the complex structure of a cycled sodium‐metal anode with the protruding candles being the dendrites. A slice, obtained by cryogenic focused ion beam (FIB) microscopy, further reveals the underlying porosity that develops during repeated plating and stripping of the metal. The thick non‐uniform red frosting on the cake represents the unstable solid electrolyte interphase (SEI) that drives the dendrite growth.